Modeling of emission lines in low-ionization winds of B-type stars - Mercanti, Lorena Verónica (2021)
Motivated by the availability of new observational material provided by Gaia mission, and focused on peculiar B-type stars, we develop a model to simulate the non-LTE line profiles of ionized elements such as Ca π and Mg II. The calculation is performed for a range of effective temperature and surface gravity, for different temperature and velocity distributions of the circumstellar material as well as different stellar mass-loss rates. The obtained synthetic profiles are capable of reproducing the general features of the observed spectral lines, such as P Cygni-type profiles.